Analysis and Design of Leaky-Wave Antenna with Low SLL Based on Half-Mode SIW Structure - Jiaying Guo; Zheng Li; Junhong Wang; Meie Chen; Zhan Zhang (International Journal of Antennas and Propagation)
This paper presents a novel leaky-wave antenna based on the Half-Mode Substrate Integrated Waveguide (HMSIW) structure with low side lobe level. The effect of the structural parameters of the LWAs on the radiation performances is studied. Using beam-forming technique, the leakage loss factor α along the radiation aperture is designed in a tapered way by controlling the aperture depth along the structure. This controls the radiated power along the antenna aperture and finally achieves the radiation pattern with low SLL. Furthermore, the antenna structure is optimized to get an even lower SLL.